The Importance of Connecting the First/Last Mile to Public Transpor - Kalasova, Alica; Culik, Kristian; Poliak, Milos (Communications - Scientific Letters of the University of Zilina, 2022)
The first and last mile part of the public transport journey are essential for the whole transport system. Its quality affects the overall experience of the passenger in public transport. It is not important how attractive are individual transport modes if the rest of the journey is unattractive for the passenger. This paper is about shared mobility and it describes the connection between the first/last mile and the public transport system. Modes of shared mobility can reduce the pressure on the city transport system. It can also bring a better modal split. The authors performed a traffic-sociological survey for processing the respondents' opinions on the use of new modes of the sharing economy. The survey showed that more than eighty per cent of people travel to work daily, but more than half of them do not use public transport.
Keywords: first-/last-mile transport; public transport; demand; city; sharing economy